Dedicated neck 18F‐FDG PET/CT: An additional tool for risk assessment in thyroid nodules at ultrasound intermediate risk. (27th February 2019) - Trimboli, Pierpaolo; Piccardo, Arnoldo; Alevizaki, Maria; Virili, Camilla; Naseri, Mehrdad; Sola, Simona; Paone, Gaetano; Russ, Gilles; Giovanella, Luca
Summary: Background: Several ultrasound (US) risk stratification systems have been proposed for the assessment of thyroid nodules, and their performance was shown as good. However, the rate of nodules assessed at intermediate risk is not negligible and whether they should be submitted or not to further examination is still under debate. The present study aimed to evaluate the reliability of 18 F‐FDG PET/CT in stratifying the risk of malignancy in these lesions. Methods: Two institutions participated to this retrospective study in which a dedicated 18 F‐FDG PET/CT was proposed to patients having a thyroid nodule with US assessment of EU‐TIRADS 4 or 5. 18 F‐FDG PET/CT did not influence the diagnostic and therapeutic decision. Histology was the gold standard for all patients. Results: Ninety‐three patients were included for the study with 48 EU‐TIRADS 4 and 45 EU‐TIRADS 5 nodules. Of these, 26 underwent thyroidectomy following FNAC suspicious for or consistent with malignancy, 38 for inconclusive cytology, 27 because of large goitre and 2 for high‐risk lesion at US. At histology, 35 carcinomas and 58 benign lesions were found. Cancer prevalence was 16.7% in EU‐TIRADS 4 and 60% in EU‐TIRADS 5. Overall, 18 F‐FDG PET/CT was positive in 33/35 cancers (94.5% sensitivity) and negative in 31/58 benign lesions (53.4% specificity). When considering only EU‐TIRADS 4, 18 F‐FDG PET/CT was positive in 7/8 cancers and negative in 20/40 benign lesions; among these, there were 36 cases with FNAC indication according to dimensional cut‐off (ie >1.5 cm), and 18 F‐FDG PET/CT showed 85.7% sensitivity and 41.4% specificity. Conclusions: 18 F‐FDG PET/CT may have a role in stratifying the cancer risk of thyroid nodules with an intermediate ultrasound assessment. More specifically, thyroid lesions classified as EU‐TIRADS 4 and with no 18 F‐FDG uptake could be ruled out from further examination, similar to other anamnestic and clinical suspicious factors of patients. Further prospective and cost‐effectiveness studies are needed.